Seasonal sleep patterns among people with early-onset psychosis and university students - Ásrún Á. Jónsdóttir 1986- (2020)
According to the literature, sleep problems are common in individuals with psychosis and seasonal change in daylight affect peoples’ sleep patterns. This study aims to investigate the relationship between seasonal change and sleep patterns in people with early-onset psychosis and university students in Iceland. Three hypotheses were tested 1) Less daylight during winter in Iceland causes worsened sleep patterns. 2) Sleep patterns in young individuals newly diagnosed with psychosis are worse in comparison to a group of healthy students in the same age group. 3) Less daylight during the winter affects patients differently than students. The participants consisted of two samples, a clinical sample of 29 individuals (21 males, 8 female) in the ages of 18-35 (mean of 25 years), admitted to Laugarás, an early onset psychosis unit at Landspítali – The National University Hospital of Iceland, and a comparison sample of 44 healthy university students (16 males, 28 females) (mean of 25 years). The participants wore actigraphy watches and logged their sleep schedule for ten days first in August/September of 2019, then again in January/February of 2020 and filled out depression and anxiety scales. There was a large dropout from the clinical group for the second measurement, leaving the clinical group of only 7 patients. The results indicate differences in sleep patterns between the two groups and that seasonal change affects sleep patterns in both groups, although differently. Patients were sleeping too much while students were sleeping too little, more in the summertime than wintertime. The three hypothesizes were all partially or fully confirmed. The results suggest that young people with early-onset psychosis could benefits from better morning routine during the summertime. Landspítali